Impacto da disseminação da informação sobre o Transtorno Do Espectro Autista: estudo misto exploratório - Ramirez, César Antonio Fabián (2024)
Autism spectrum disorder, also known by its abbreviation ASD, is a condition characterized by persistent deficits in two major areas: 1) social communication and social interaction; and 2) restricted and repetitive patterns of behavior, interests, and activities. This study evaluated the impact of disseminating information about autism to family members and caregivers of autistic children. This research was configured as a longitudinal exploratory mixed study (qualitative followed by quantitative). This type of research is focused on the emergence of new ideas and analysis of contexts so that the researcher has greater proximity to the subject. In the qualitative stage, the informational demands of the population on autism spectrum disorder were mapped in two scenarios, one in the Southeast and the other in the North region of Brazil. At this stage, it was observed that the main informational demands of the population about autism spectrum disorder are: family support, self-realization, characteristics of autism spectrum disorder, diagnosis, self-care features, affective features, cognitive features, communicational features, occupational features, origin of autism spectrum disorder, prejudice, treatment and cure. In the quantitative stage, eight informational contents were disseminated to 73 participants, caregivers of autistic children during the psychological consultation, in 2024, in the Northern Region of Brazil. In the dissemination process, the companions evaluated each of the contents, totaling 584 evaluations regarding the eight informational contents disseminated. Among the most significant findings, it is worth highlighting that the study participants claim that the information disseminated taught them something new (319, 54.6%), encouraged them to learn more about the subject (251, 43.0%), helped them to better understand autism (435, 74.6%) and prepared them to discuss autism with other people (361, 61.9%). As a contribution to the field of Information Science, knowledge was explained and systematized that can guide institutions, services and information systems that prioritize the care of the community involved with autism spectrum disorder.